Physicochemical characterization of microwave-stabilized rice bran oil from Ethiopian small-scale rice-processing plants - Bultum, Lemessa Etana; Emire, Shimelis Admasu; Tufa, Lemma Teshome (Frontiers in Food Science and Technology, 2022)
Rice bran is one of the main byproducts of rice-processing industries, making approximately 10% of the total mass of rice kernels. It is rich in bioactive phytochemicals, which have several health benefits. Among others, rice bran contains 10%–23% oil, constituting the major bioactive elements of the bran. The aim of this work is therefore to evaluate rice bran oil obtained from Ethiopian small-scale rice-milling plants for suitability of human consumption. The rice bran was stabilized using microwave heating to inactivate endogenous lipase enzymes that would otherwise cause rancidity of the oil and render it inedible. The oil was then extracted and evaluated for its physicochemical properties, fatty acid composition, and antioxidant activity using standard methods. The result of the work confirmed that the rice bran oil from Ethiopian rice-milling plants has physicochemical characteristics that satisfy the acceptable threshold values set by various organizations. Interestingly, the oil contained a substantial fatty acid profile (high amount of unsaturated fatty acids) and a high content of unsaponifiable matter which contributes to the claimed health benefits of the oil. In addition, it exhibited a strong antioxidant activity (95.319%) at a concentration of 18 mg/ml, which also essentially contributes to its health benefits. Proper integration of rice milling with byproduct utilization such as rice bran oil production will contribute to the efforts to alleviate the oil scarcity in the country.